2011
DOI: 10.1126/scitranslmed.3003126
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal/Permeability-Increasing Protein (rBPI 21 ) and Fluoroquinolone Mitigate Radiation-Induced Bone Marrow Aplasia and Death

Abstract: Identification of safe, effective treatment strategies to mitigate toxicity after extensive radiation exposure has proven challenging. Only a limited number of candidate approaches have emerged, and the Federal Drug Administration has yet to approve any agent for a mass-casualty radiation disaster indication. As preparative treatments for hematopoietic stem cell transplantation (HSCT) produce toxicities similar to such radiation exposures, we studied patients early after myeloablative HSCT to identify new appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 54 publications
2
43
0
Order By: Relevance
“…Recently, novel mechanisms have been described that may be targeted to mitigate radiation injury to the hematopoietic system (5,6,8,32,33). To our knowledge, PTN represents the first therapeutic demonstrated to improve survival when administered more than 24 hours after exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, novel mechanisms have been described that may be targeted to mitigate radiation injury to the hematopoietic system (5,6,8,32,33). To our knowledge, PTN represents the first therapeutic demonstrated to improve survival when administered more than 24 hours after exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Radiation causes toxicity to hematopoietic stem cells (HSCs) through the generation of ROS, induction of DNA strand breaks and apoptosis, and damage to the BM microenvironment (2)(3)(4). Despite an understanding of mechanisms through which ionizing radiation causes hematopoietic toxicity, few effective mitigators of radiation-induced hematopoietic injury have been developed (5)(6)(7)(8)(9). The lack of effective mitigators for acute radiation sickness (ARS) has become a public health concern, as the risk of terrorism using radiological or nuclear devices has escalated (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Even a moderate dose (eg, 3 Gy) of IR exposure can cause acute myelosuppression characterized by neutropenia, lymphocytopenia, and thrombocytopenia. It is well documented that hematopoietic acute radiation syndrome increases the risk of infection, bleeding, and even death [4][5][6][7][8][9]. Moreover, during the course of radiation and chemotherapy, therapyinduced myelosuppression may cause high mortality and morbidity and worsen the outcome of cancer treatment [2,[4][5][6][7][8].…”
mentioning
confidence: 99%
“…It is well documented that hematopoietic acute radiation syndrome increases the risk of infection, bleeding, and even death [4][5][6][7][8][9]. Moreover, during the course of radiation and chemotherapy, therapyinduced myelosuppression may cause high mortality and morbidity and worsen the outcome of cancer treatment [2,[4][5][6][7][8]. Studies from ours and other laboratories have demonstrated that radiation-caused acute myelosuppression is largely attributable to the induction of apoptosis in hematopoietic stem and progenitor cells (HSPCs) [3,6].…”
mentioning
confidence: 99%
“…The hematopoietic system is highly sensitive to IR, and in particular, IR doses beyond 2 Gy can lead to myelosuppression that is characterized by neutropenia, lymphocytopenia, and thrombocytopenia. Collectively, hematopoietic acute radiation syndrome (H-ARS) increases the risk of infection, bleeding, and death (1)(2)(3)(4)(5)(6)(7)(8)(9). There is an unmet need for effective interventions to mitigate the progression of H-ARS after IR exposure (10).…”
Section: Introductionmentioning
confidence: 99%